DNS blocking in KW: pornhub.com, tiktok.com, xvideos.com (Kuwait) - Voidly (2026)
CRITICAL severity censorship detected in Kuwait. Confidence: 85%. Data sourced from CensoredPlanet.
Censorship Incident ID: KW-2026-0003
Keywords: censorship; KW; censorship; critical